COST ANALYSIS OF CERVICAL CANCER MEDICAL TREATMENT AS A CONSIDERATION IN DETERMINING THE HEALTH COSTING DUE TO INA-DRGs AT RSUD Dr. MOEWARDI - Devi Oktaviani; Iwan Dwiprahasto; Tri Murti Andayani (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The implementation of INA-DRGs system for the third-class patients of Jamkesmas (Public Health Insurance Program) in hospital is expectedly able to increase the access and the health service quality for the poor and underprivileged people in effectively and efficiently realizing the optimal health service. This research was aimed to obtain the average cost of medical treatment of cervical cancer and also learn the compatibility between cost of medical treatment of cervical cancer in RSUD Dr. Moewardi and the constancy of INA-DRGs based health financing. This was a descriptive research under the perspective of hospital. Data was collected retrospectively by investigating the medical record document of patients with cervical cancer and the data of the medical treatment cost of patients. The research subject was cervical cancer case with the third-class patients of JAMKESMAS in RSUD Dr. Moewardi in the period of January-July 2010 that was in line with the inclusion criteria. Further, the data analysis was done by cross tab with Chi Square test and by comparing the average cost and ALOS (Average length of stay) through the constancy of INA-DRG. The Chi Square Test shows a correlation between LOS, patient factor (the number of parities), and disease factors (co-morbidity and severity level) with the health care cost for cervical cancer in RSUD. Dr. Moewardi. The health care average cost of cervical cancer based on the tariff of RSUD Dr. Moewardi for the severity level I included: IDR2.893.243 for surgery, IDR3.313.342 for chemotherapy, IDR3.988.027 for radiotherapy and IDR10.039.072 for radical hysterectomy. Meanwhile, in the severity level II, it included IDR5.885.859 for surgery, IDR4.474.084 for chemotherapy. In the severity level III, it includes IDR13.347.209 for radical hysterectomy. The ALOS was longer compared to ALOS of INA-DRG except in the severity level III. This then gives an effect on the health care cost for cervical cancer that in general was higher than the tariff of INA-DRG. In conclusion, implementation of INA-DRG for the treatment of cervical cancer in patients of JAMKESMAS in RSUD Dr. Moewardi was in efficient.Keywords: INA-DRG, cervical cancer, JAMKESMAS